1998
DOI: 10.1046/j.1432-1327.1998.2510304.x
|View full text |Cite
|
Sign up to set email alerts
|

A stress‐inducible rat liver endoplasmic reticulum protein, ERp29

Abstract: We have isolated, cDNA cloned and characterised a 29-kDa protein (ERp29), containing a C-terminal endoplasmic reticulum(ER)-retrieval signal, from the rat liver ER. ERp29 was induced to high levels in the rat hepatoma cells under metabolic stress conditions known to cause an aberrant accumulation of proteins in the ER [(e.g. culture in presence of the Ca 2ϩ ionophore A23187, inhibitors of Ca 2ϩ -ATPase (thapsigargin), intracellular protein transport (brefeldin A), or protein N-glycosylation (tunicamycin)]. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
104
2
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 7 publications
9
104
2
4
Order By: Relevance
“…Rabbit anti-MOSC2 and anti-CYB5B antibodies were from Atlas Antibodies (Stockholm Sweden); mouse anti-mHSP70 and rabbit anti-VDAC were from Affinity Bioreagents (Thermo Scientific); and rabbit anti-CYB5 was from Santa Cruz Biotechnology (AH Diagnostics AB, Skärholmen, Sweden). Rabbit anti-CYB5R3 (16), rabbit antiERp27 (17), and rabbit anti-calnexin (18) were previously described. Secondary horseradish peroxidase-coupled antirabbit and anti-mouse antibodies were from Dako (Dako Sweden AB, Stockholm, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit anti-MOSC2 and anti-CYB5B antibodies were from Atlas Antibodies (Stockholm Sweden); mouse anti-mHSP70 and rabbit anti-VDAC were from Affinity Bioreagents (Thermo Scientific); and rabbit anti-CYB5 was from Santa Cruz Biotechnology (AH Diagnostics AB, Skärholmen, Sweden). Rabbit anti-CYB5R3 (16), rabbit antiERp27 (17), and rabbit anti-calnexin (18) were previously described. Secondary horseradish peroxidase-coupled antirabbit and anti-mouse antibodies were from Dako (Dako Sweden AB, Stockholm, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…15 Endoplasmic reticulum protein 29 (ERp29), a novel reticuloplasmin, was first cloned from rat liver and enamel cells. 16,17 Structurally, it has an ER-retrieval signal of the Cterminal tetrapeptide (KEEL) targeting the ER lumen, but lacks the classical chaperone, disulfide-editing, calcium-buffer, and stress-response properties. 18 It has been shown that ERp29 is directly associated with the folding and/or secretion of thyroglobulin, 19 as well as resistance to oxidative and radiation stress.…”
mentioning
confidence: 99%
“…Quality control of potential cargo proteins is accomplished by the molecular chaperones that monitor fidelity of the protein folding and prevent premature export of incorrectly folded or incompletely assembled secretory proteins from the ER (2). Circumstantial evidence, such as inducibility in certain cell types under the ER stress conditions (3), high expression in the secretory tissues (4,5), and co-localization with the ER chaperones (3), suggests that a recently discovered, ubiquitously expressed endoplasmic reticulum lumenal protein, ERp29, may complement this group of ER chaperones.…”
mentioning
confidence: 99%
“…ERp29 cDNA was originally cloned from the rat liver (3,6) and enamel cells (7), and the ERp29 gene was shown to be highly conserved in all studied mammalian species (3)(4)(5). For instance, rat ERp29 and its human ortholog, originally termed ERp28 (8), are 90% identical on the amino acid sequence level (9).…”
mentioning
confidence: 99%